ON THE BIOMETRY, FOOD AND FEEDING AND SPAWNING HABITS OF OTOLITHES RUBER (SCHNEIDER) FROM PORTO NOVO - Pillai, P K Mahadevan (Indian Journal of Fisheries, 2011)
Out of the 17 morphometric characters studied, the distance between thetip of snout and insertion of anal fin was observed to have the fastest growth ratein Otolithes ruber (Schneider) along the Porto Novo coast. O. ruber, highly carnivorous,shows a selectivity of feeding. The ova-diameter frequency suggests thatspawning takes place in O. ruber only once a season, for a shoh duration